Industry 4.0 and intelligent manufacturing technologies - Mrugalska, Beata; Karwowski, Waldemar, 1953-; Ahram, Tareq Z. (Routledge, 2025)
The world is undergoing a transformation driven by Industry 4.0 and intelligent manufacturing technologies. This book explores aspects of well-being and collaboration in industrial systems which were underscored by automation and security focus.Industry 4.0 and Intelligent Manufacturing Technologies explores the different ways in which technology disrupts and revolutionizes industrial management. It discusses the connection between engineering, science, and management, aiming to assist companies, researchers, and professionals navigate and excel in this transformation era. This book offers insights by examining Industry 4.0 and intelligent manufacturing technologies. It looks into the driving forces behind digitalization, automation, intelligent process control, artificial intelligence, and additive manufacturing. Lastly, the book showcases the seamless integration of advanced digital technologies into manufacturing and industrial processes.This book aims to attract managers and researchers to the field of industrial engineering. It also offers valuable insights for students, graduates, and educators focusing on industrial and business management. However, the content is not exclusive to these audiences and will be engaging for any reader with an interest in the subject matter.
Keywords: Industry 4.0.; Computer integrated manufacturing systems.; Artificial intelligence -- Industrial applications.; Industrial management -- Technological innovations.; Manufacturing processes -- Technological innovations.; elektronické knihy; electronic books